Epitaxy: a methodological approach to the study of an old phenomenon. Issue 23 (27th May 2022) - Bruno, M.; Pastero, L.; Cotellucci, A.; Aquilano, D.
Abstract : We describe the use of an integrated methodological approach to study epitaxial phenomena. Abstract : Epitaxial growth is a long-standing crystallization phenomenon of great technological interest. Here, we present the use of a new methodology approach making full use of the concept of adhesion energy between two different crystal phases, A and B. This is achieved by using (i) the traditional crystal-chemical fit between A and B; (ii) the extensive use of Bollmann's approach to the 2D-lattice coincidences; (iii) the most accurate methods of calculation of the specific adhesion energy of A/B. We illustrate the approach with two case studies: (i) how epilayers of inorganic and monoclinic Li2 CO3 (zabuyelite) can modify the crystal habit of the CaCO3 polymorphs, calcite (rhombohedral) and aragonite (orthorhombic); (ii) how a complex organic substance like sericin (silk fibroin like protein-SFLP) could stabilize aragonite and calcite, the most diffuse CaCO3 polymorphs, simply reproducing and mimicking in the laboratory what nature does.